2015
DOI: 10.3390/polym7091480
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Non-Compression X-Bracing Systems Using Carbon Fiber Composite Cable for Seismic Strengthening of RC Buildings

Abstract: Cross-bracing (X-bracing) is one of the most popular methods of seismic retrofitting, and has been shown to significantly increase the structural stiffness and strength of buildings. Conventional steel X-bracing methods typically exhibit brittle failure at the connection between the brace and the building, or buckling failure of the braces. This study investigated the structural properties of a new type of non-compression X-bracing system using carbon fiber composite cable (CFCC). This non-compression X-bracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several studies demonstrated that through the use of steel braces enhances the seismic performance of the strengthened frame improving strength, stiffness and energy dissipation capacity. A specific category in the brace strengthening technique of existing RC frames concerns the use of X-type cable elements [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that through the use of steel braces enhances the seismic performance of the strengthened frame improving strength, stiffness and energy dissipation capacity. A specific category in the brace strengthening technique of existing RC frames concerns the use of X-type cable elements [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of the provided stirrups is rather low (∅6/200 mm) and their efficiency should be checked. The absence of significant vertical gravity loads on the columns has as result the appearance of alternative axial forces (positive and negative, not only negative ones) as is the case of only compressive axial forces reported in the literature [11,13,19]. A preliminary simulation has given for these alternative axial forces the order results of the about values from -48 kN to +37 kN for the columns and from -67 kN to +55kN for the beam.…”
Section: The Finite Element (Fe) Discretization Of the Rc Framesmentioning
confidence: 89%
“…An alternative technique that uses cable-like members as tension-ties instead of the common steel bracing has been proposed for seismic strengthening of RC frames [12,13]. Cable restrainers have also been used for concrete and steel superstructure movement joints in bridges [14].…”
Section: Introductionmentioning
confidence: 99%
“…The input seismic ground motion was set to 200 cm/s 2 using the Hachinohe wave (EW), under which the reference frame with no reinforcement applied underwent a collapse. Figure 28 shows the RC school building model before and after seismic strengthening, and the amount of seismic strengthening needed for the NBSD seismic control system was calculated by Equations ( 11)- (13). The equations were derived from the Newmark's equal energy criterion [51,52], which is the same method used by Japan to evaluate seismic energy absorption of seismic devices [7].…”
Section: Overview Of the Nonlinear Dynamic Analysismentioning
confidence: 99%
“…In attempts to addressing the disadvantages of conventional repair and retrofitting methods, as mentioned above, research has been actively carried out since the early 1990s on retrofitting methods using new composite materials, such as carbon fiber, Aramid fiber, and glass fiber [12][13][14][15][16]. These methods, however, also come with disadvantages as follows [16]:…”
mentioning
confidence: 99%